Developing a phenomenological model to simulate single and mixed scale formation during flow in porous media: Coupling a salt precipitation model with an ion transport equation under dynamic conditions - Erfan Hosseini; Dana Mohammad Nazar; Negar Hosseini; Mohammad Sarmadivaleh (Petroleum Research, 2024)
Water flooding and pressure maintenance are recommended to improve oil recovery practices after low recovery of petroleum reservoirs occurs during primary production. Salt crystal formation is a frequent occurrence when using these techniques. Several experimental, numerical, and theoretical studies have been done on the mechanisms underlying scaling and permeability reduction in porous media; however, there has not been a satisfactory model developed. This study developed a phenomenological model to predict formation damage caused by salt deposition. Compared with existing models, which provide a scaling tendency, the proposed model predicts the profile of scale deposition. The salt precipitation model simulates reactive fluid flow through porous media. A thermodynamic, kinetic, and flow hydrodynamic model was developed and coupled with the ion transport equation to describe the movement of ions. Further, a set of carefully designed dynamic experiments were conducted and the data were compared with the model predictions. Model forecasts and experimental data were observed to have an average absolute error (AAE) ranging from 0.68% to 5.94%, which indicates the model's suitability.